2015
DOI: 10.3402/gha.v8.29738
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends of postpartum family planning in Ethiopia, Malawi, and Nigeria: evidence of missed opportunities for integration

Abstract: BackgroundThe first 12 months following childbirth are a period when a subsequent pregnancy holds the greatest risk for mother and baby, but also when there are numerous contacts with the healthcare system for postnatal care for mother and baby (immunisation, nutrition, etc.). The benefits and importance of postpartum family planning are well documented. They include a reduction in risk of miscarriage, as well as mitigation of (or protection against) low birth weight, neonatal and maternal death, preterm birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 9 publications
(14 reference statements)
11
66
2
1
Order By: Relevance
“…[812, 24] Postpartum FP use in LMICs has also been associated with urban residence,[8] being married,[12] greater wealth and education,[1012] achievement of desired family size and current fertility desire. [24] In contrast to our study, a study conducted in five LMICs found that younger postpartum women (<20 years old) were 24% more likely than women ≥30 years to have an unmet need for FP.…”
Section: 0 Discussionmentioning
confidence: 99%
“…[812, 24] Postpartum FP use in LMICs has also been associated with urban residence,[8] being married,[12] greater wealth and education,[1012] achievement of desired family size and current fertility desire. [24] In contrast to our study, a study conducted in five LMICs found that younger postpartum women (<20 years old) were 24% more likely than women ≥30 years to have an unmet need for FP.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Sexually active women reporting modern contraceptive use increased from 66% at the time of the 3-month survey to 86% at the time of the 6-month survey and 91% at the 12-month survey. Demographic and Health Surveys (DHS) data from Malawi shows that approximately 14% of women are using modern methods of contraception by 3 months after delivery, though this was higher among urban women[7]. The women included in this analysis had high levels of education and were mostly from urban areas in Lilongwe district, which has been shown to have higher postpartum family planning use than most districts in Malawi[8].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the vast majority of postpartum women in developing countries missed the opportunities at each points of contacts [8,10]. With this, postpartum women are among those with the greatest unmet need for family planning than other periods [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the vast majority of postpartum women in developing countries missed the opportunities at each points of contacts [8,10]. With this, postpartum women are among those with the greatest unmet need for family planning than other periods [6,10,11]. In Ethiopia, unmet need for family planning in the postpartum period is also much higher than women outside of the extended postpartum period; while 16.2% women, in general, do have unmet need for family planning [12], the unmet need in the first year after childbirth reaches as high as 44 percent [13].…”
Section: Introductionmentioning
confidence: 99%